Safety of motorized two-wheeler riders in the formal and informal transport sector. Issue 1 (2nd January 2020) - Gutierrez, Maria Isabel; Mohan, Dinesh
Abstract: Road fatalities are largely preventable problem with large socioeconomic impact. Due to the rapidly increasing population, transport systems and road infrastructure have not met the demand. The use of motorized two-wheeler vehicles has increased, as informal transport. However, evidence on their safety is scarce. The aim of this article is to examine the safety and social equity issues in MTW in the informal transport sector. Factors can be used to explain traffic collisions in MTW in the formal/informal transport sectors: design, rider behavior, road design, enforcement, and regulation of the informal transport sector. Evidence suggests that MTWs could be a common related to pedestrian fatalities. Informal transport drivers are typically poor, uneducated, young men who due to lack of other employment options move into the informal sector. Their vehicles are old, unmaintained and have a lack of protective equipment for themselves and their passengers. Young, male drivers speed, take risks and not use protective equipment. Users of informal transport live in the poorer peripheries of cities, which, have limited, inefficient or unaffordable public transport. The provision of transport has therefore become an often unrecognized, important social equity issue and studies are urgently needed on MTW in the informal transport sector.